Metaphorical Reﬂections on the Colonial Circus of the Drunken Indian and the Kidney Machine - Koptie, Steven; Wesley-Esquimaux, Cynthia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
This paper represents the need for First Nations community workers to share their narratives of experience and wisdom for academic review. A growing number of mature Indigenous social service workers are returning to Canada’s learning centers where they are articulating observations and insights to Indigenous experience in colonial Canada. It is imperative that post-colonial academic literature include these contributions. True reconciliation between Canada and First Peoples is only possible if those stories of resilience are reﬂected back from the experience of historic trauma and unresolved intergenerational suffering.